P2M‐based security model: security enhancement using combined PUF and PRNG models for authenticating consumer electronic devices. Issue 6 (21st September 2018) - Wortman, Paul; Yan, Wei; Chandy, John; Tehranipoor, Fatemeh
Abstract : Continued growth and development in the consumer electronic market have greatly increased in the realm of home automation. With this swelling in smart, Internet‐connected consumer electronics, there is a need to ensure the safe and secure use of these products. So how does one authenticate each product in a large connected environment? How can the authors minimise counterfeiting, cloning, and the presence of Trojans in customer electronics? In this study, they explore their method of using various physically unclonable functions (PUFs) as a potential seed for a pseudorandom number generators (PRNGs) element. These can then be used to authenticate consumer electronic devices or protect communication over a large interconnected network. The advantage of this work is that their method increases the difficulty of attackers to learn patterns of the seed of each PRNG while optimising PUF‐based constraints in different consumer electronic domains. Through this work they enhance the function of PRNGs, increasing the difficulty of attackers' ability to model security systems, as well as present a lightweight and efficient solution to the growing security concerns. By making the PRNG more difficult to model, malicious actors are less able to overcome their proposed security enhancement leading to a safe and secure environment.